MENINGKATKAN KETERAMPILAN BERBICARA SISWA BELAJAR BAHASA INGGRIS MELALUI PENGGUNAAN MEDIA PEMBELAJARAN INVITATION PADA SISWA KELAS VIII A SMP NEGERI 3 MUARA BUNGO - Liniswarti lini Liniswarti (Jurnal Tunas Pendidikan, 2021)
ABSTRACT The problem in this study is that speaking skills related to students' pronunciation are still not in line as they should be. In reality, students are still weak in speaking correctly. The method used in this research is Classroom Action Research, with the research subjects being students of SMP Negeri 3 Muara Bungo. The results of the study stated that the average achievement of each task from each group in the first cycle was 66 and the second cycle was 78. There was an average increase in students' speaking skills in learning English for all assignments in groups I, II, III, IV, V and VI. is 20, 20, 20, 40, 40, 10. The ratio of the increase is as follows 20: 20: 20: 40: 40: 10 = 150 or 13%: 13%: 13%: 27%: 27%: 7%. The comparison of the average increase in the speaking skills of students learning English in the first cycle and the second cycle is 66: 78 = 144 or 46: 54 = 100. The conclusion of this study is that the speaking skills of students learning English can increase if using invitation learning media (Invitation). ). Keywords: speaking skill, English, invitation